ANALISIS PRODUKSI PERIKANAN, NILAI TUKAR NELAYAN, DAN INFRASTRUKTUR PELABUHAN SEBAGAI DETERMINAN KESEJAHTERAAN NELAYAN DI ACEH - Azwar Azwar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
Fisherfolk welfare is a strategic issue in coastal economic development in Aceh. This study aims to analyze the relationship between capture fisheries production, Fishermen’s Terms of Trade (FTT/NTN), the availability of fishery port infrastructure, and the contribution of the fisheries subsector to Aceh’s GRDP during 2020–2024. A quantitative descriptive approach was applied using secondary data from BPS, the Aceh Marine and Fisheries Office, as well as provincial development planning documents (RPJM and Renstra). The results indicate that Aceh’s capture fisheries production shows an overall increasing trend despite annual fluctuations, with the highest production recorded in 2022. The Fishermen’s Terms of Trade have significantly improved since 2021 and consistently remained above the welfare threshold (FTT 100). The fisheries subsector contributes steadily to the regional economy, maintaining a share of 5.15–5.63% of Aceh’s GRDP. Additionally, the presence of 26 fishery ports plays a crucial role in enhancing supply chain efficiency, stabilizing fish prices, and improving product competitiveness. This study concludes that the welfare of fisherfolk is influenced not only by production volume but also by infrastructure effectiveness, market stability, and fisheries governance. Policy implications emphasize the need for port modernization, cold-chain strengthening, livelihood diversification, and coordinated stakeholder collaboration to sustainably enhance fisherfolk welfare in Aceh.